Ivabradina, insufficienza cardiaca e malattia renale cronica - Giovanni Barbera; Alberto Santoboni; Antonio De Pascalis; Rodolfo Rivera; Fulvio Floccari; Claudio Ronco; Luca Di Lullo (AboutScience Srl, 2015)
Abstract non disponibile (Cardionephrology)